Renewable Energy and Kaliandra Plant Utilization for Eco Edu Tourism - Nasython, Kun (CV. Publikasi Indonesia, 2025)
This research investigates the multifaceted potential of Kaliandra plant cultivation beyond its established use as a renewable energy source for wood pellets. The study highlights Kaliandra's significant capacity to enhance local economic income through eco-tourism, emphasizing the strategic role of direct and indirect benefits in empowering local communities by involving them as eco-tourism actors. Furthermore, the research underscores Kaliandra's crucial contribution to reducing carbon emissions. By integrating Kaliandra cultivation with eco-tourism and educational initiatives, the study concludes that the